Ultra-high-strength steel with a low carbon footprint and method for manufacturing the same

JP2026534215APending Publication Date: 2026-10-14BAOSHAN IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026517657
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-25
Filing Date
2024-09-24
Publication Date
2026-10-14

Smart Images

  • Figure 2026534215000008
    Figure 2026534215000008
  • Figure 2026534215000001
    Figure 2026534215000001
  • Figure 2026534215000002
    Figure 2026534215000002
Patent Text Reader

Abstract

The present invention discloses an ultra-high-strength steel with a low carbon footprint, wherein the ultra-high-strength steel contains Fe and unavoidable impurities, and further contains the following chemical elements in the following mass percentages: C: 0.06-0.12%, Si: 0.2-0.6%, Mn: 1.7-2.3%, Mo: 0.14-0.22%, Nb: 0.02-0.05%, Ti: 0.03-0.07%, Al: 0.02-0.06%, B: 0.001-0.003%, and N: 0.005-0.01%. The N distribution coefficient in the ultra-high-strength steel is N 固溶 / N 析出 The value is ≥4. The present invention further provides a method for manufacturing the ultra-high-strength steel. The ultra-high-strength steel of the present invention combines the technological advantages of being green, low-carbon, high-strength, and lightweight.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to steel plates and methods for manufacturing the same, and more particularly to ultra-high-strength steel and methods for manufacturing the same. [Background technology]

[0002] In recent years, advanced high-strength steel for automobiles has been widely adopted to achieve vehicle weight reduction, energy saving and emission reduction, improved collision safety, and reduced manufacturing costs. By increasing the strength of the steel sheet, it is possible to reduce the thickness of the steel sheet while maintaining excellent formability.

[0003] With the development of high-strength steel technology, attention is not only being paid to improving its mechanical properties, but also to the expectation that it will combine high strength, light weight, and be green and low-carbon.

[0004] A Chinese patent document with publication number CN113215477A, ​​publication date August 6, 2021, and disclosure title "Method for Manufacturing Low-Carbon Dioxide Emission Cold-Rolled Base Steel Strip" discloses a method for manufacturing low-carbon dioxide emission cold-rolled base steel strip, the process flow of which is upper-bottom composite blow converter smelting, removal of inclusions by slag during converter tapping, continuous slab casting, and hot continuous rolling, and discloses a method for manufacturing cold-rolled deep-drawn base steel strip containing low carbon, low silicon, and boron. By omitting the LF refining process, the nitrogen content in the steel is reduced, electrode wear in the production process is eliminated, and power consumption and carbon dioxide emissions are reduced.

[0005] A Chinese patent document with publication number CN115058641A, publication date September 16, 2022, and disclosure title "Method for producing low-sulfur, low-aluminum, high-carbon wire rod steel by electric furnace smelting of 100% scrap steel" discloses a method for producing low-sulfur, low-aluminum, high-carbon wire rod steel by electric furnace smelting of 100% scrap steel, and the method belongs to the metallurgical technology field and includes the processes of electric furnace smelting, LF refining, RH vacuum refining, and continuous casting. In the electric furnace smelting process, 100% scrap steel is used as raw material, and silicon iron, carbon extender, manganese iron, other alloys, and slag material are added in that order during tapping.

[0006] It is clear that none of the above patent documents relate to low-carbon footprint technology.

[0007] A Chinese patent document with publication number CN115433855A, publication date December 6, 2022, and disclosure title "Aluminum extruded profiles with a low carbon footprint" discloses aluminum extruded profiles with a low carbon footprint and also provides the components of an alloy composition, in which approximately 60% of the alloy composition is derived from Al scrap. However, this patent document belongs to the field of aluminum alloys and does not relate to low carbon footprint steel materials. [Overview of the Initiative]

[0008] One objective of this invention is to provide an ultra-high-strength steel with a low carbon footprint that has a unique compositional design, a low carbon equivalent, employs a low-carbon emission steelmaking process consisting of an electric furnace-LF furnace-RH-continuous casting, and uses scrap steel as the smelting raw material instead of molten iron, which consumes a lot of carbon, thereby providing an ultra-high-strength steel that satisfies certain formability and bending characteristics while combining the technological advantages of being green, low-carbon, high-strength, and lightweight.

[0009] To achieve the above objective, the present invention provides an ultra-high-strength steel with a low carbon footprint, containing Fe and unavoidable impurities, and further containing the following chemical elements in the following mass percentages, namely, C: 0.06 to 0.12%, Si: 0.2 to 0.6%, Mn: 1.7 to 2.3%, Mo: 0.14 to 0.22%, Nb: 0.020 to 0.050%, Ti: 0.03 to 0.07%, Al: 0.02 to 0.06%, B: 0.0010 to 0.0030%, N: 0.0050 to 0.0100%, and The N partition coefficient in the above ultra-high strength steel is N 固溶 / N 析出 Provided is an ultra-high strength steel satisfying ≧4.00.

[0010] Correspondingly, the present invention is an ultra-high strength steel with a low carbon footprint, wherein the mass percentage content of each chemical element is C: 0.06 to 0.12%, Si: 0.2 to 0.6%, Mn: 1.7 to 2.3%, Mo: 0.14 to 0.22%, Nb: 0.020 to 0.050%, Ti: 0.03 to 0.07%, Al: 0.02 to 0.06%, B: 0.0010 to 0.0030%, N: 0.0050 to 0.0100%, with the balance being Fe and unavoidable impurities, The N partition coefficient in the above ultra-high strength steel is N 固溶 / N 析出 Provided is an ultra-high strength steel satisfying ≧4.00.

[0011] Note that, for the ultra-high strength steel grade N according to the present invention 析出 In the measurement method, inclusions are separated from the target material by electrolytic extraction, and then the N content in the inclusions is determined as N 析出 measured as, and N 固溶 =N 総 -N 析出 and N 総 is the total N content in the material measured by the GB / T 20124 inert gas fusion thermal conductivity method.

[0012] In the present invention, the N content tends to be high due to the adoption of an electric furnace smelting process. When N is present in the matrix in a solid solution state, it improves the strength of the material, but when it is present in a precipitated state, it exists as TiN inclusions, and if the inclusion content is too high, it affects the plasticity and bending properties of the material. Therefore, in the hot-rolled high-strength steel according to the present invention, the mass percentage content of N is controlled to 0.0050 to 0.0100%, and the N distribution coefficient is set so that N exists in a solid solution state as much as possible. 固溶 / N 析出 Control to ≥4.00. In some embodiments, N 固溶 / N 析出 The range is 4.00 to 6.00. In some embodiments, N 固溶 ≥ 0.0040, for example, in the range of 0.0040 to 0.0090, or in the range of 0.0040 to 0.0085. In some embodiments, N 析出 The range is ≤0.0020, for example, in the range of 0.0005 to 0.0015, or in the range of 0.0008 to 0.0015.

[0013] Furthermore, in the ultra-high-strength steel according to the present invention, the design principles for each chemical element are specifically as follows.

[0014] C: In the ultra-high-strength steel according to the present invention, carbon directly affects the strength, weldability, and formability of the steel sheet / strand, and a higher carbon content is advantageous for improving the strength of the steel sheet. If the carbon content is less than 0.06%, the strength of the steel sheet / strand will not reach the target, and if the carbon content exceeds 0.12%, the carbon equivalent will be too high, which may worsen the weldability of the steel sheet. Therefore, in the ultra-high-strength steel according to the present invention, the mass percentage content of carbon can be controlled in the range of 0.06 to 0.12%, and in some embodiments, the mass percentage content of C can be controlled in the range of 0.08 to 0.11%.

[0015] Si: In the ultra-high-strength steel according to the present invention, the Si element is dissolved in ferrite and plays a role in solid solution strengthening. Furthermore, the Si element promotes the concentration of C and Mn elements into austenite in ferrite, reducing interstitial solid solution strengthening and suppressing the formation of coarse carbides during cooling, thereby improving the ductility of the steel. However, the Si element is prone to concentrated oxidation on the surface of the steel strip during annealing, forming an SiO2 oxide film, which is difficult to reduce with hydrogen and affects surface quality. Moreover, if the Si element content is too high, it also adversely affects the spot welding characteristics of the steel sheet. Therefore, in the ultra-high-strength steel according to the present invention, the mass percentage content of silicon can be controlled in the range of 0.2 to 0.6%, and in some embodiments, the mass percentage content of Si can be controlled in the range of 0.3 to 0.6%.

[0016] Mn: In the ultra-high-strength steel according to the present invention, the element Mn is a solid-solution strengthening element and a good desulfurizing agent, which is advantageous for improving the strength of the steel. Furthermore, Mn enriches in austenite and plays a stabilizing role, which is advantageous for improving the plasticity of the steel. Therefore, in the ultra-high-strength steel according to the present invention, the mass percentage content of Mn can be controlled in the range of 1.7 to 2.3%, and in some embodiments, the mass percentage content of Mn can be controlled in the range of 1.9 to 2.1%.

[0017] Mo: In the ultra-high-strength steel according to the present invention, the Mo element is a carbide element and also plays a role in promoting improved hardenability of austenite, shifting the transformation regions of ferrite, pearlite, and bainite to the right and expanding the austenite region. However, if the Mo content is high, problems such as cracking of the edges during cold rolling are more likely to occur, making the manufacturability of the material difficult. Therefore, in the ultra-high-strength steel according to the present invention, the mass percentage content of Mo can be controlled in the range of 0.14 to 0.22%, and in some embodiments, the mass percentage content of Mo can be controlled in the range of 0.16 to 0.20%.

[0018] Nb: In the ultra-high strength steel according to the present invention, the Nb element plays an important role in grain refinement, and the fine carbonitride formed by combining Nb with C and N delays recrystallization, prevents the growth of crystal grains, and brings a significant strengthening effect. Therefore, in the ultra-high strength steel according to the present invention, the mass percent content of Nb can be controlled in the range of 0.020 to 0.050%, and in some embodiments, the mass percent content of Nb can be controlled in the range of 0.025 to 0.045%.

[0019] Ti: In the ultra-high strength steel according to the present invention, Ti fixes nitrogen in the steel to form a stable compound, improves slab quality and edge crack defects, further forms fine carbides, inhibits the growth of austenite crystal grains, and can refine the crystal grains. Therefore, in the ultra-high strength steel according to the present invention, the mass percent content of Ti can be controlled in the range of 0.03 to 0.07%, and in some embodiments, the mass percent content of Ti can be controlled in the range of 0.04 to 0.06%.

[0020] Al: In the ultra-high strength steel according to the present invention, when Al exists in a solid solution state, it suppresses the precipitation of cementite and improves the stability of austenite. Furthermore, Al forms finely dispersed sparingly soluble particles with C and N, and can refine crystal grains. However, if the Al content in the steel is too high, a large amount of oxide inclusions are easily formed, which is detrimental to the cleanliness of molten steel. Therefore, in the ultra-high strength steel according to the present invention, the mass percent content of Al can be controlled in the range of 0.02 to 0.06%, and in some embodiments, the mass percent content of Al can be controlled in the range of 0.02 to 0.05%.

[0021] B: In the ultra-high-strength steel according to the present invention, the main role of element B is to improve the hardenability of the steel and increase the strength of the steel material. B tends to segregate at austenite grain boundaries, delaying the transformation from austenite to ferrite, and has a significant effect even at low concentrations. At the same time, B has a good grain boundary purifying effect, inhibiting the segregation of harmful elements at grain boundaries to a certain extent, and improving the deformation coordination of the material. However, if the B content is too high, the strength of the steel increases, making it difficult to obtain good plasticity. Therefore, in the ultra-high-strength steel according to the present invention, the mass percentage content of B can be controlled in the range of 0.0010 to 0.0030%, and in some embodiments, the mass percentage content of B can be controlled in the range of 0.0020 to 0.0030%.

[0022] Furthermore, the ultra-high-strength steel according to the present invention further contains one or more of Cr, Ni, Cu, and V. When these are included, the Cr content is 0.05 wt% or less, the Ni content is 0.05 wt% or less, the Cu content is 0.10 wt% or less, and the V content is 0.05 wt% or less.

[0023] In some embodiments, the ultra-high-strength steel according to the present invention further includes the following items, namely: Cr ≤ 0.05 wt%, Ni ≤ 0.05 wt%, Cu ≤ 0.1 wt%, It contains at least one residual element in an amount of V ≤ 0.05 wt%.

[0024] In this invention, since 100% scrap steel is used as smelting raw material, residual elements Cr, Ni, Cu, and V, which are difficult to remove during steelmaking, may be introduced into the raw material. Of these, if the levels of Cr and Ni are too high, the phase transformation law of the material changes; if the level of Cu is too high, it causes copper brittleness problems during hot rolling; and if the level of V is too high, it generates many precipitates and increases the material strength. Therefore, it is necessary to control the levels of Cr, Ni, Cu, and V within the above ranges.

[0025] Furthermore, the unavoidable impurities in the ultra-high-strength steel according to the present invention are P ≤ 0.015%, S ≤ 0.0030%, and Sn ≤ 0.010%.

[0026] In the present invention, unavoidable impurities mainly include phosphorus (P), sulfur (S), and tin (Sn), and the lower the content of these impurities, the purer the steel and the better its performance. Of these, if the P content is too high, the grain boundaries weaken, the brittleness of the material increases, and the weldability deteriorates. Therefore, in the ultra-high-strength steel according to the present invention, the mass percentage content of P can be controlled to P ≤ 0.015%. If the S content in steel is too high, the plasticity of the material deteriorates significantly. Therefore, in the ultra-high-strength steel according to the present invention, the mass percentage content of S can be controlled to S ≤ 0.0030%. Sn is also a harmful element in steel, and when it segregates at grain boundaries, it adversely affects the toughness and plasticity of the material. Furthermore, if the Sn content is too high, the coating properties of the material also deteriorate. Therefore, in the ultra-high-strength steel according to the present invention, the Sn content can be controlled to Sn ≤ 0.010%.

[0027] Furthermore, in the ultra-high-strength steel according to the present invention, the harmful element factor Hem ≤ 0.0180%, where Hem = Sn + N / 2 + 2S, and each chemical element in the formula is substituted in terms of its mass percentage content.

[0028] In this invention, the bending and hole-expanding properties of the material can be further guaranteed by controlling the harmful element factor to Hem ≤ 0.0180%.

[0029] Furthermore, in the ultra-high-strength steel according to the present invention, the weld carbon equivalent Ceq ≤ 0.280%, and Ceq = C + Mn / 20 + Si / 30 + 2P + 4S, where each chemical element in the formula is substituted in terms of its mass percentage content.

[0030] In the present invention, the mass percentage content of C, Si, Mn, P, and S is the weld carbon equivalent C eq When ≤0.280% is satisfied, better welding properties are obtained, and the solid solution and structural strengthening effects of the material in that component are good, resulting in higher material strength. In some embodiments, C eq≤0.250%. In some embodiments, C eq ≤0.240%. In some embodiments, C eq The range is 0.220% to 0.240%.

[0031] Furthermore, in the ultra-high-strength steel according to the present invention, the mass percentage content of each chemical element is further specified in the following items, namely: C: 0.08~0.11%, Si: 0.3~0.6%, Mn: 1.9~2.1%, Mo: 0.16~0.20%, Nb: 0.025~0.045%, Ti: 0.04~0.06%, Al: 0.02~0.05%, B: Satisfies at least one of the following conditions: 0.0020-0.0030%.

[0032] Furthermore, in the ultra-high-strength steel according to the present invention, the microstructure includes ferrite and martensite.

[0033] Furthermore, in the ultra-high-strength steel according to the present invention, the volume phase ratio of martensite is 60-75%.

[0034] Furthermore, in the ultra-high-strength steel according to the present invention, the yield strength is 700 to 850 MPa, the tensile strength is ≥ 980 MPa, preferably ≥ 1020 MPa, the elongation at break is ≥ 10.0%, preferably ≥ 13.0%, the 180-degree cold bending characteristics guarantee that no cracks occur under 1T conditions (i.e., no cracks occur even when the washer is 1x the plate thickness), and the carbon footprint is ≤ 1.2 kgCO2eq / kg. In some embodiments, the ultra-high-strength steel according to the present invention has a tensile strength of 980 to 1100 MPa. In some embodiments, the ultra-high-strength steel according to the present invention has a uniform elongation of ≥ 6.0%.

[0035] Another objective of the present invention is to provide a method for manufacturing ultra-high-strength steel with a low carbon footprint, which is green and highly efficient, and in which the manufactured ultra-high-strength steel combines the advantages of being green, low-carbon, high-strength, and lightweight.

[0036] To achieve the above objective, the present invention provides a method for manufacturing ultra-high-strength steel with a low carbon footprint, comprising the following steps, namely: In the RH process, the vacuum treatment time is ≤10 min, for example, 3 to 10 min, and after vacuum breaking, soft blowing is performed for 15 to 25 min. This is electric furnace smelting, LF, RH, and continuous casting using all scrap steel. Hot rolling and winding, Cold rolling and, This invention presents a manufacturing method that includes continuous annealing, first by holding the annealing temperature at 760-820°C for 60-200 seconds, then cooling to a rapid cooling start temperature of 650-690°C at a first cooling rate of 3-10°C / s, further cooling to a rapid cooling end temperature of 220-260°C at a second cooling rate of 40-80°C / s, then holding the temperature for 200-400 seconds for aging treatment, and finally cooling to below 100°C at a third cooling rate of 2-10°C / s.

[0037] The smelting and casting process of the present invention specifically includes an electric furnace-LF furnace-RH-continuous casting process. Conventional blast furnace converter manufacturing processes are lengthy and employ a coke-based iron ore reduction method, resulting in a significantly high carbon footprint for the final product, basically at the 2.5-3.0 kgCO2eq / kg level. Furthermore, the ironmaking and steelmaking processes account for nearly 70% of the entire process, making them the part with the highest carbon footprint. In addition, conventional electric furnace smelting is widely applied to medium- and high-carbon steels and stainless or special steel products, and is hardly involved in high-strength steels for medium- and low-carbon automobiles, where the control of impurity elements such as low S and low N is necessary.

[0038] This invention significantly reduces carbon dioxide emissions in the steelmaking process by employing 100% scrap steel electric furnace smelting. Furthermore, this invention employs a short vacuum time and a long soft blow time in RH. In some embodiments, the vacuum is drawn down to 100 Pa or less, the vacuum is maintained for 10 minutes or less, then the vacuum is broken, and after the vacuum is broken, soft blowing is performed for 15 to 25 minutes. The soft blowing effect is based on the principle of not damaging the slag surface, and then, for example, after being left to stand for 10 minutes, the material is lifted into a continuous casting machine and cast.

[0039] In this invention, vacuum treatment can reduce the nitrogen content in molten steel, but if the vacuum treatment time is too long, the reduction in nitrogen content becomes less significant, and prolonged vacuum treatment is unfavorable for the plastic deformation of inclusions. Prolonged soft blowing after vacuum breaking can remove inclusions (mainly nitride and sulfide inclusions) or plasticize them. Therefore, in the RH vacuum refining process, the inclusion and gas content can be effectively controlled by employing a short vacuum time and a long soft blowing time. Since the nitrogen content when scrap steel is tapped in an electric furnace is clearly higher than in the conventional converter process, the RH treatment can set the controllable lower limit of nitrogen to the 50 ppm level, and the treatment can significantly remove TiN inclusions in the molten steel, essentially leaving them in the slag.

[0040] Furthermore, in the method for manufacturing ultra-high-strength steel according to the present invention, the deformed structure after cold rolling is held at an annealing temperature of 760-820°C for 60-200 seconds to perform two-phase annealing. The main purpose of this process is to recrystallize the steel sheet structure after cold rolling. If the temperature is too low, the recrystallization of the steel sheet structure will be incomplete, and if the temperature is too high, it will cause grain coarsening and decomposition of precipitates in the steel sheet structure, leading to a decrease in steel sheet strength. Therefore, in the present invention, the annealing temperature is controlled to 760-820°C. Similarly, time control is also very important in this process. If the time is too short, the recrystallization of the steel sheet structure will be incomplete, and the diffusion of austenite-stabilizing elements (C, Mn) will be insufficient. On the other hand, if the time is too long, it is easy to cause abnormalities such as abnormal grain coarsening and decomposition of precipitates in the steel sheet structure, so the annealing time is controlled to 60-200 seconds. During this process, the steel sheet structure undergoes partial austenitization, while the cold-rolled deformed grains complete the recovery and recrystallization process.

[0041] Furthermore, by controlling the cooling rate of the steel strip after heat retention to a first rate of 3-10°C / s and slowly cooling it to 650-690°C, some of the austenite in the steel sheet structure can be transformed into ferrite first, and the ferrite in this portion is finer than the recrystallized ferrite in the two-phase region. This is advantageous for improving the coordination of the two phases, the soft phase and the hard phase, and the plasticity of the material during final deformation.

[0042] Furthermore, the second cooling rate is controlled to 40-80°C / s, and the steel strip, which has been slowly cooled by air blow rapid cooling, is rapidly cooled to 220-260°C, and then kept warm for 200-400 seconds for aging treatment. In this process, if the cooling rate is too slow, pearlite will form and the properties of the steel sheet will deteriorate, while if the cooling rate is too fast, it will lead to increased production difficulty and manufacturing costs, so the second cooling rate is controlled to 40-80°C / s. In the rapid cooling process, most of the remaining austenite is transformed into martensite, and the strength is greatly improved. In the aging process, the quenched martensite undergoes a low-temperature tempering reaction, and a small amount of the layered martensite obtained by quenching decomposes, causing carbides to precipitate, which is advantageous for improving the toughness of the material and avoiding the occurrence of cold brittle fracture.

[0043] Furthermore, after aging treatment, the steel strip is cooled to below 100°C at a third cooling rate of 2-10°C / s, and below this temperature, the steel's structure essentially stops changing.

[0044] Furthermore, in the electric furnace smelting process of the method for producing ultra-high-strength steel according to the present invention, the scrap steel used includes three types: light scrap steel, medium scrap steel, and heavy scrap steel, and the weight ratio of these is light scrap steel:medium scrap steel:heavy scrap steel = (3~3.5):(1.5~2):1.

[0045] In this specification, light scrap steel refers to finished scrap steel in block form or irregular shape, trimmed pieces, and similar materials, with a size of less than 300 x 800 x 1800 mm and a unit weight of 0.5 tons or less. Medium scrap steel refers to various machine scrap steel components, parts, and similar materials in block form or irregular shape, with a size of less than 300 x 500 x 1500 mm and a unit weight of 1.0 ton or less. Heavy scrap steel refers to block ingot scrap, bloom scrap, and similar materials, with a size of less than 300 x 500 x 1500 mm and a unit weight of 2.0 tons or less.

[0046] In the electric furnace smelting process described herein, clean and pure scrap steel is selected. Before introducing the scrap steel raw material, 1 to 2 tons of light scrap steel is first laid on the bottom of the electric furnace as a lining to prevent impact and damage to the furnace lining when a large amount of scrap steel (especially heavy scrap steel) is introduced. In the smelting process, oxygen gas is blown in using a high-flow oxygen lance to promote melting and dephosphorization, and the final components of the electric furnace are controlled to C ≤ 0.05 wt%, P ≤ 0.01 wt%, and S ≤ 0.03 wt%, while simultaneously T 出鋼 The temperature is controlled to be ≥1630℃. After tapping, the steel is sent to the slag removal station for slag removal, and the amount of residual slag is controlled to be ≤40mm.

[0047] In some embodiments, in the LF process, after the ladle arrives at the LF station, Al is first added to perform advanced deoxidation. After confirming that Al ≥ 0.03 wt% by sampling analysis, carbon extender, iron silicate, and iron manganese are added to replenish carbon and perform deoxidation alloying, while slag material is added to perform slag desulfurization. In this specification, the slag material can be lime and fluorite, and by adding 6-8 kg / t of lime to steel and 1-2 kg / t of fluorite to steel, the slag basicity can be suitably controlled to 1.8-2.5, and the sulfur content can be desulfurized to 30 ppm or less. After desulfurization is complete, the necessary Nb, Ti, and B alloy components are added. After all alloy components have been added, preparations are made to leave the station, and at the same time, excess desulfurized slag is discharged, controlling the residual slag amount to ≤ 30 mm.

[0048] Furthermore, in the continuous casting process of the method for manufacturing ultra-high-strength steel according to the present invention, the degree of superheating is controlled to 30°C or less, the mold taper to 1.0-1.3%, and the continuous casting and drawing speed to 1.0-1.5 m / min.

[0049] In the continuous casting process of the present invention, the molten steel needs to have a certain degree of superheating in order for the continuous casting process of molten steel to proceed smoothly. If the degree of superheating exceeds 30°C, it is detrimental to the quality of the interior of the slab center, and defects such as segregation and shrinkage cavities are likely to occur. Therefore, in the present invention, the degree of superheating can be controlled to ≤30°C, for example, to 15-30°C. At the same time, in order to better control the slab surface quality and prevent defects such as small longitudinal cracks, a chamfered mold is selected to improve the stress distribution and the mold taper is controlled to a range of 1.0-1.3%. In order to balance production efficiency and slab surface quality, the continuous casting and drawing speed is controlled to a range of 1.0-1.5 m / min. In the casting process, dynamic light reduction and electromagnetic stirring are used to further improve the degree of segregation of the slab.

[0050] Furthermore, in the hot rolling process of the method for manufacturing ultra-high-strength steel according to the present invention, the slab heating temperature is controlled to 1200-1260°C, and the finish rolling completion temperature is controlled to 850-950°C.

[0051] In the hot rolling process of the present invention, the slab is first heated to a high temperature throughout the entire austenite region to soften the material and allow the components to diffuse completely and uniformly. After rough rolling to the thickness of the intermediate slab, the coarse structure generated in the heating furnace is crushed and refined, and then by finishing rolling to a predetermined thickness, a uniform and fine recrystallized material structure is formed. If the finishing rolling end temperature is below 850°C, ferrite precipitates before finishing rolling, the hard phase content in the final structure becomes low, the strength in the hot-rolled state is insufficient, and this affects the subsequent cold-rolling annealing performance. Considering the upper limit control of the slab heating temperature and the temperature drop in the rolling process, the finishing rolling end temperature usually does not exceed 950°C. Therefore, in the present invention, the finishing rolling end temperature can be controlled to 850-950°C.

[0052] Furthermore, in the winding process of the ultra-high-strength steel manufacturing method according to the present invention, the winding temperature is controlled to 580 to 660°C.

[0053] In this invention, the hot-rolling winding temperature also affects the performance of the hot-rolled state. If the winding temperature exceeds 660°C, internal oxidation of Si and Mn is likely to occur on the steel sheet surface, and a surface fracture layer is formed by pickling, affecting the surface quality of the final product. On the other hand, if the winding temperature is below 580°C, the strength of the hot-rolled state is too high, which is disadvantageous for the subsequent cold-rolling process, and the deformation resistance becomes too large, causing problems such as edge cracking and sheet shape defects during cold rolling. Therefore, preferably, in this invention, the winding temperature can be controlled to 580-660°C.

[0054] Furthermore, in the cold rolling process of the method for manufacturing ultra-high-strength steel according to the present invention, the cold rolling reduction ratio is controlled to 50-70%.

[0055] In this invention, after removing the surface oxide scale of the hot-rolled coil by pickling, the steel sheet is brought to the target thickness by cold rolling with a reduction of 50-70%, and a certain amount of deformation energy is accumulated, which is advantageous for subsequent annealing and recrystallization.

[0056] The low-carbon footprint ultra-high-strength steel and its manufacturing method according to the present invention have the following advantages and beneficial effects.

[0057] The ultra-high-strength steel with a low carbon footprint according to the present invention is controlled by a specific composition design to have a low carbon equivalent and to have as much nitrogen as possible in a solid solution state, and the nitrogen distribution coefficient is set to N 固溶 / N 析出 By controlling it to ≥4.00, the strength of the material is improved, while also ensuring the plasticity and bending properties of the material.

[0058] The present invention provides a method for producing ultra-high-strength steel with a low carbon footprint, which employs an electric furnace 100% scrap steel smelting technology route. This ensures that the produced ultra-high-strength steel has the technological advantages of being green and low-carbon. Furthermore, by controlling the scrap steel raw materials and steelmaking technology, impurities and residual elements in the product are kept at low levels, without affecting the material's performance.

[0059] The present invention provides a method for producing ultra-high-strength steel with a low carbon footprint. In contrast to the electric furnace all-scrap steel smelting route, which is characterized by a high nitrogen content, the RH process is controlled in such a way that most of the nitrogen is present in the material in a solid solution state. This improves the strength of the material while maintaining its local formability.

[0060] In several embodiments, the low-carbon footprint ultra-high-strength steel according to the present invention has a yield strength of 700-850 MPa, a tensile strength of ≥980 MPa, a fracture elongation of ≥10%, and a 180-degree cold bending characteristic of not fracturing under 1T conditions (i.e., not fracturing even when the washer is 1x the plate thickness), while simultaneously achieving a carbon footprint of ≤1.2 kgCO2eq / kg, thus realizing both green, low-carbon and ultra-high-strength performance. [Brief explanation of the drawing]

[0061] [Figure 1] Figure 1 shows the microstructure morphology of a low-carbon footprint ultra-high-strength steel according to Example 7 of the present invention. [Modes for carrying out the invention]

[0062] The low-carbon-footprint ultra-high-strength steel and its manufacturing method according to the present invention will be further interpreted and described below in conjunction with specific examples, but such interpretation and description will not inappropriately limit the embodiments of the present invention.

[0063] Examples 1-20 and Comparative Examples 1-3 The low-carbon footprint ultra-high-strength steels of Examples 1 to 20 of the present invention were all manufactured using the following process.

[0064] (1) Electric furnace smelting, LF, RH and continuous casting using 100% scrap steel: In the electric furnace smelting process, the total amount of scrap steel consists of three types: light scrap steel, medium scrap steel, and heavy scrap steel, and clean and well-maintained scrap steel is selected. Before introducing the scrap steel raw materials, 1 to 2 tons of light scrap steel is first laid on the bottom of the electric furnace as a lining to prevent impact and damage to the furnace lining when a large amount of scrap steel (especially heavy scrap steel) is introduced. In the smelting process, oxygen gas is blown in using a high-flow oxygen lance to promote melting and dephosphorization, and the final components of the electric furnace are controlled to C ≤ 0.05 wt%, P ≤ 0.01 wt%, and S ≤ 0.03 wt%, while simultaneously T 出鋼 The temperature is controlled to be ≥1630℃. After tapping, the steel is sent to the slag removal station for slag removal, and the amount of residual slag is controlled to be ≤40mm.

[0065] In a preferred embodiment, the weight ratio of the three types of scrap steel is light scrap steel:medium scrap steel:heavy scrap steel = (3-3.5):(1.5-2):1.

[0066] In the LF process, after the ladle arrives at the LF station, Al is first added to perform advanced deoxidation. After confirming that Al ≥ 0.03 wt% by sampling analysis, carbon extender, iron silicate, and iron manganese are added to replenish carbon and perform deoxidation alloying, while slag material is added to perform slag desulfurization. Here, the slag material is lime and fluorite, and the amount of lime added is 6-8 kg / t of steel, and the amount of fluorite added is 1-2 kg / t of steel, thereby controlling the slag basicity to a suitable 1.8-2.5 and enabling desulfurization of the sulfur content to 30 ppm or less. After desulfurization is complete, the necessary Nb, Ti, and B alloy components are added. After all alloy components have been added, preparations are made to leave the station, and at the same time, excess desulfurized slag is discharged, controlling the residual slag amount to ≤ 30 mm.

[0067] In the RH process, after the RH arrives at the station, a vacuum is drawn down to 100 Pa or less, the vacuum is maintained for 10 minutes or less, then the vacuum is broken. After the vacuum is broken, soft blowing is performed for 15 to 25 minutes, with the soft blowing effect being just enough so as not to damage the slag surface. After that, it is left to stand for about 10 minutes, then lifted into the continuous casting machine and cast.

[0068] In the continuous casting process, the superheating degree was controlled to 15-30°C, the mold taper to 1.0-1.3%, and the continuous casting and drawing speed to 1.0-1.5 m / min. The chemical composition content of the resulting slabs is shown in Tables 1-1, 1-2, and 1-3.

[0069] (2) Hot rolling and coiling: The slab heating temperature is 1200-1260°C. After rough rolling, finish rolling is performed, with the finish rolling completion temperature being 850-950°C. After rolling, the slab is water-cooled to a coiling temperature of 580-660°C.

[0070] (3) Remove the oxide scale by pickling. (4) Cold rolling: A reduction of 50-70% is used.

[0071] (5) Continuous annealing: The annealing temperature is maintained at 760-820°C for 60-200 seconds, then cooled to a rapid cooling start temperature of 650-690°C at a first cooling rate of 3-10°C / s to obtain a certain percentage of ferrite. Next, it is rapidly cooled to a rapid cooling end temperature of 220-260°C at a second cooling rate of 40-80°C / s. After that, it is held for 200-400 seconds for aging treatment. Finally, it is cooled to below 100°C at a third cooling rate of 2-10°C / s.

[0072] [Table 1-1]

[0073] [Table 1-2]

[0074] [Table 1-3]

[0075] In Tables 1-1, 1-2, and 1-3, steel grades A to E are the steel grade numbers used in the embodiments of the present invention, and a to c are the steel grade numbers used in the comparative examples.

[0076] Tables 2-1 and 2-2 show the specific process parameters in the above-mentioned step for each example and comparative example of the present invention.

[0077] [Table 2-1-1]

[0078] [Table 2-1-2]

[0079] [Table 2-2]

[0080] For the samples obtained in Examples 1-20 and Comparative Examples 1-3, polished, smooth surfaces free of visible scratches were etched using a 4% nitric acid alcohol solution. The etching solution was wiped off with a clean cotton ball for approximately 15 seconds, and the microstructure was observed. Bright, white areas in the microstructure are ferrite structures, and fine, dark structures are martensite structures. The observation results are shown in Table 3.

[0081] Furthermore, Figure 1 shows the microstructure of the low-carbon footprint ultra-high-strength steel of Example 7 of the present invention. As shown in Figure 1, the microstructure of the low-carbon footprint ultra-high-strength steel is ferrite + martensite.

[0082] Furthermore, the samples obtained for Examples 1-20 and Comparative Examples 1-3 were subjected to ISO 6892:1998 (Method for room temperature tensile testing of metallic materials) and P14(A 50 Mechanical property tests were performed according to the tensile sample specifications, and the carbon footprint was calculated. The results are shown in Table 3. Here, the calculation boundary for the product carbon footprint is cradle-to-gate, and the specific calculation method and product classification follow ISO 14067 "Greenhouse gases - Carbon footprint of products - Requirements and guidelines for quantification" and the Japan Steel Manufacturers Association EPD Platform PCR 2022:01 "Ordinary steel products and special steel products".

[0083] [Table 3]

[0084] As can be seen from Table 3, Examples 1 to 20 of the present invention achieved ideal microstructure characteristics through a combination of rational chemical elemental composition design and optimized process parameters. While ensuring strength, plasticity was also excellent, with yield strength in the range of 700 to 850 MPa, tensile strength of 980 MPa or higher in all cases, uniform elongation of 6.0% or higher in all cases, and elongation at break of 10.3% or higher in all cases. Furthermore, the 180-degree cold bending characteristics were excellent, and all cases met the requirement of no fracture under 1T conditions.

[0085] At the same time, the carbon footprint levels of Examples 1 to 20 of the present invention are all 1.2 kg CO2eq / kg or less, indicating low carbon dioxide emission levels and meeting the technical requirements for green and low carbon. On the other hand, the process route of Comparative Example 1 still uses the conventional converter route and blast furnace molten iron, resulting in a high carbon footprint.

[0086] Unlike the present invention, each comparative example failed to achieve the technical effects achievable by the present invention because its components or process parameters did not meet the design requirements of the present invention.

[0087] Furthermore, the combination methods of each technical feature in this application are not limited to the combination methods described in the claims of this application or the combination methods described in the specific embodiments. All technical features described in this application can be freely combined or combined in any manner, as long as they do not contradict each other.

[0088] Furthermore, the embodiments described above are merely specific examples of the present invention. The present invention is not limited to the above embodiments, and similar changes or modifications can be obtained from or easily conceived by those skilled in the art from the content disclosed herein, and are within the scope of protection of the present invention.

Claims

1. A low-carbon-footprint ultra-high-strength steel containing Fe and unavoidable impurities, further containing the following chemical elements in the following mass percentages, namely, The composition is as follows: C: 0.06–0.12%, Si: 0.2–0.6%, Mn: 1.7–2.3%, Mo: 0.14–0.22%, Nb: 0.020–0.050%, Ti: 0.03–0.07%, Al: 0.02–0.06%, B: 0.0010–0.0030%, N: 0.0050–0.0100%. The N distribution coefficient in the aforementioned ultra-high-strength steel is N 固溶 / N 析出 Ultra-high-strength steel characterized by satisfying the value ≥ 4.

00.

2. The ultra-high-strength steel sheet according to claim 1, wherein the mass percentage content of each chemical element is: An ultra-high-strength steel sheet characterized by having the following composition: C: 0.06–0.12%, Si: 0.2–0.6%, Mn: 1.7–2.3%, Mo: 0.14–0.22%, Nb: 0.020–0.050%, Ti: 0.03–0.07%, Al: 0.02–0.06%, B: 0.0010–0.0030%, N: 0.0050–0.0100%, with the remainder being Fe and unavoidable impurities.

3. The ultra-high-strength steel sheet according to claim 1 or 2, further comprising the following items, namely: Cr ≤ 0.05 wt%, Ni ≤ 0.05 wt%, Cu ≤ 0.10 wt%, An ultra-high-strength steel sheet characterized by containing at least one residual element in an amount of V ≤ 0.05 wt%.

4. An ultra-high-strength steel sheet according to claim 1 or 2, characterized in that, among unavoidable impurities, P ≤ 0.015%, S ≤ 0.003%, and Sn ≤ 0.01%.

5. An ultra-high-strength steel sheet according to claim 4, characterized in that the harmful element factor Hem ≤ 0.018%, where Hem = Sn + N / 2 + 2S, and each chemical element in the formula is substituted by its mass percentage content, and / or the weld carbon equivalent Ceq ≤ 0.28%, where Ceq = C + Mn / 20 + Si / 30 + 2P + 4S, and each chemical element in the formula is substituted by its mass percentage content.

6. The ultra-high-strength steel sheet according to claim 1 or 2, wherein the mass percentage content of each chemical element is further specified as follows: C:0.08~0.11%、 Si: 0.3–0.6%, Mn: 1.9–2.1%, Mo: 0.16–0.20%, Nb: 0.025–0.045%, Ti: 0.04–0.06%, Al:0.02~0.05%、 B: An ultra-high-strength steel sheet characterized by satisfying at least one of the following conditions: 0.002% to 0.003%.

7. An ultra-high-strength steel sheet according to claim 1 or 2, characterized in that the microstructure comprises ferrite and martensite, and preferably the volume phase ratio of martensite is 60 to 75%.

8. An ultra-high-strength steel sheet according to claim 1 or 2, wherein the yield strength is 700 to 850 MPa, the tensile strength is ≥ 980 MPa, the elongation at break is ≥ 10.0%, the 180-degree cold bending characteristic is guaranteed not to break under 1T conditions, and the carbon footprint is ≤ 1.2 kgCO 2 An ultra-high-strength steel sheet characterized by having a strength of eq / kg, preferably a tensile strength of ≥1020 MPa, and preferably a uniform elongation of ≥6.0%.

9. A method for manufacturing ultra-high-strength steel with a low carbon footprint according to any one of claims 1 to 8, comprising the following steps, namely: In the RH process, the vacuum treatment time is ≤10 min, and after vacuum breaking, soft blowing is performed for 15-25 min. This is electric furnace smelting using all scrap steel, LF, RH, and continuous casting. Hot rolling and winding, Cold rolling and, A manufacturing method characterized by comprising continuous annealing, in which the material is first kept warm at an annealing and holding temperature of 760 to 820°C for 60 to 200 seconds, then cooled to a rapid cooling start temperature of 650 to 690°C at a first cooling rate of 3 to 10°C / s, further cooled to a rapid cooling end temperature of 220 to 260°C at a second cooling rate of 40 to 80°C / s, then kept warm for 200 to 400 seconds for aging treatment, and finally cooled to below 100°C at a third cooling rate of 2 to 10°C / s.

10. A manufacturing method according to claim 9, characterized in that, in the electric furnace smelting step, the scrap steel used includes three types: light scrap steel, medium scrap steel, and heavy scrap steel, and the weight mixing ratio thereof is light scrap steel:medium scrap steel:heavy scrap steel = (3 to 3.5):(1.5 to 2):

1.

11. A manufacturing method according to claim 9, characterized in that in the LF step, the slag baseness is set to 1.8 to 2.5 so that the S content is removed to within 30 ppm.

12. A manufacturing method according to claim 9, characterized in that, in the continuous casting process, the degree of superheating is controlled to 30°C or less, the mold taper to 1.0 to 1.3%, and the continuous casting and drawing speed to 1.0 to 1.5 m / min.

13. A manufacturing method according to claim 9, characterized in that, in the hot rolling step, the slab heating temperature is controlled to 1200 to 1260°C and the final rolling temperature for finish rolling is controlled to 850 to 950°C.

14. A manufacturing method according to claim 9, characterized in that the winding temperature is controlled to 580 to 660°C during the winding step.

15. A manufacturing method according to claim 9, characterized in that, in the cold rolling step, the cold rolling reduction ratio is controlled to 50 to 70%.